INFORMATION-ANALYTICAL AND LEAGAL ACTIVITY IN SMALL BUSINESS MANAGEMENT SYSTEM - Долішній, Богдан Семенович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article highlights the specific of information management in the management of small businesses (SB), which requires a systematic approach not only to the analysis of primary data, but also to its generalization in accordance with the cyclical phases (stages) management solutions, structure of government, previous experience in solving problematic situations and other. The interaction of object and subject management.